La figura del facilitatore linguistico: un’esigenza dei contesti scolastici plurilingui per la comunicazione tra agenzie formative, docenti, studenti e famiglie. I risultati di un’indagine - Nitti, Paolo; Grosso, Micaela (Rivista Italiana di Educazione Familiare, 2020)
The presence of learners with a migrant background requires the educational system to be geared especially with regards to educational communication. In the school context, there has recently been a transition from a situation of greater stability to a context in which change and therefore discontinuity are on the agenda. This brings great opportunities thanks to the multitude of stimuli presented and offered to students, but at the same time a dangerous risk of early school leaving. The essay will discuss some data of educational and language educational nature, related to a multidisciplinary research, started from 2019/2020, related to the communication between schools, teachers, students, and their families, during SARS-CoV-2 health emergency.